Developmental outcome after intravascular intrauterine transfusion for rhesus haemolytic disease. Issue 1 (January 1994) - Stewart, G; Day, R E; Del Priore, C; Whittle, M J; Turner, T L; Holland, B M
Abstract : The development outcome of 16 infants who had rhesus disease was assessed at 18 months. Eight had received intravascular intrauterine transfusion and eight postnatal exchange transfusions. There was no difference in developmental outcome and neither group was different from the population as a whole.